Adjustment problem and associated factors among first-year undergraduates at Wollo University, Ethiopia - Anbesaw, Tamrat; Beyene, Abeba; Kefale, Jerusalem (Frontiers in Education, 2022)
Background Adjustment problems are characterized by a maladaptive emotional response to a stressful event among fresh first-year students. In Ethiopia, there is limited evidence about the adjustment problem and its determinant factors among undergraduates. Therefore, the present study aimed to assess the prevalence of adjustment problems and associated factors among first-year undergraduates at Wollo University, Dessie, Ethiopia. Methods An institutional-based cross-sectional study design was conducted from February 1–20, 2020. A systematic random sampling technique was employed to select the study participants. The resultant adjustment problem was assessed using the student adjustment to college questionnaire (SACQ). Data were analyzed using SPSS version 26. Logistic regression analysis was performed, and variables with a p-value of <0.05 were taken as statistically significant with adjustment problems. Results The prevalence of adjustment problems among first-year undergraduates were found to be 41.4% (95% CI (35.8, 46.9). Students whose hometowns were far (>901 km) from the university, monthly pocket money ≤1,000 ETB, being away from family/home for the first time, and facing great difficulty living in a dormitory were significantly associated with adjustment problems among university students. Conclusion The prevalence of adjustment problems among Wollo University students was high and positively associated with students' hometowns being far (>901 km) from the university, having monthly pocket money, being away from family/home for the first time, and facing great difficulty in living in a dormitory. Therefore, establishing adjustment problem screening services on the campus and designing proper mental health intervention programs are recommended to tackle the problem.